805 UPPER LIMB FRACTURE PATHWAYS IN FRAILTY ENABLE EARLIER RETURN TO FUNCTION WITH ASSOCIATED REDUCED LENGTH OF HOSPITAL STAY. (8th March 2022) - Shaw, L; Maggs, T; Braude, P; Shipway, D; Srivastava, S; Kelly, M
Abstract: Introduction: Upper limb fractures are the second most common fracture requiring admission to hospital after hip fracture [Jennison, 2019]. At 1-year 20.5% have died, compared to 29.5% in hip fracture [Wiedl, 2021]. Local Problems: At North Bristol Trust most patients with upper limb fractures and a Clinical Frailty Score ≥ 5 are managed non-operatively on medical wards. Local service evaluation identified a long length of stay of 23 days. Case note review revealed: Delayed transfers of care (DTOCs) had been managed non-weight bearing in slings for 4–6 weeks. Non-weight bearing status resulted in DTOC due to declined access to social care and rehabilitation due to perceived health needs. A high rate of hospital-acquired complications and failure to rehabilitate. Breakdown in interdisciplinary communication and ownership across the pathway. Methods: A multidisciplinary QI project was commenced. Using local data through business analytics, clinician and patient feedback, a new Trust guideline was developed for older people with frailty and upper limb fractures. Data collected determined average length of stay before and after implementation of the service change. A standard process control chart was created monitoring the effect of the changes in the pathway. The multidisciplinary team met regularly to make alterations during implementation. The resulting intervention included: Removal of functional restrictions; allow free use of limb as comfort permits. Simplified slings and minimised light weight casts. Proactive integration of orthopaedic plan into CGA documentation. Proactive interdisciplinary communication across pathways. Patient information leaflets. Results: Pre-intervention average length of stay was 23 days. Post-intervention was 14 days. Conclusion: Proactive, structured management of upper limb fractures in people with frailty is associated with significant reduction in acute hospital length of stay. Next steps include a business case for a frailty trauma specialist therapist embedded into medicine.